The relationship between information systems resources and information security / Norizan Anwar, Prof Madya Dr. Mohamad Noorman Masrek and Yanty Rahayu Rambli - Anwar, Norizan; Masrek, Mohamad Noorman; Rambli, Yanty Rahayu (Research Management Institute (RMI), 2012)
Over the last decades, studies on Information Systems Resources and Information Security have been very rigorous among information systems (IS) researchers and scholars. Generally, previous studies have defined and identified Information Systems Resource as either a single entity of a composite entities made of several components. According to Chang and Wang (2010), Information Systems Resources can be divided into three categories which are information technology resources (ITR) (e.g., information systems expertise and skills), relationship resources (RR) (e.g., collaboration with other functional units) and IS infrastructure resources (IIS) (e.g., collection of IT assets). Ross et al. (1996) however, divided Information Systems Resources into three IT assets which are human assets (e.g., hardware and software skills, business understanding, operation-solving orientation), technology assets (e.g., IT hardware assets, hardware and software platforms, databases, architectures, standards) and relationship assets (e.g., collaboration with other divisions or functional units, internal and external client relationships, share holders, shared risk and responsibility). Mining the literature unveiled that there are many studies that have been done to investigate the relationship between Information Systems Resources and information securities within organizations. Gerber et al. (2001) described Information Security is a cycle which involves securing and controlling data and or information from any editing, changes, deleting or viewing activities by protecting and also controlling those data and or information from unauthorized personnel across department in an organization. . Among the various studies that have explored the connection between information systems resources and information systems securities are Ross et al. (1996); Byrd et al. (2004); Ravichandran & Lertwongsatien (2005); Flowerday & von Solms (2005); Chang & Ho (2006); Livari & Huisman (2007) Paschke et al., (2008); and Chang & Wang (2010). All of these studies have apparently developed models or framework that illustrates the connection or relationship between Information Systems Resources and Information Security.